Dynamic capabilities for new product development: an extended discussion of conceptual framework on Malaysia manufacturing sector - Ahmad Zaidi, Mohamad Faizal (2017)
The concept of dynamic capabilities (DCs) is commonly known as the firm’s ability to reconfigure internal resources under rapidly changing environment.Due to the multidimensional nature of the concept, DCs have been studied in various disciplines and setups.One of the disciplines is new product development (NPD). In previous year, a study of DCs focusing on the relationships between organizational resources (i.e., exploitative capability, explorative capability, structural ambidexterity, and contextual ambidexterity) and NPD performance (i.e., financial and nonfinancial) was empirically investigated with the moderating effect of environmental turbulence (i.e., market turbulence, technological turbulence, and competitive intensity) in the Malaysia manufacturing sector by Zaidi and Othman (2015).Despite of the valuable findings and contributions, this previous empirical study was only briefly addressing the conceptual framework, due to the need to pay more attention on the empirical research, e.g., methodology, analysis, and findings. Since the explanation on the concept was very minimal, this paper aims to extend the discussion on the conceptual framework in Zaidi and Othman (2015) with more attention given to explain the concept in the context of Malaysia manufacturing sector. Subsequently, this paper also elaborates on the recommendations for future studies in reflection to the previous findings. This paper enhances the contributions of previous study and improves our understanding on the concept of DCs in the relationships between organizational resources and NPD performance under environmental turbulence. At the end, this paper contributes to DCs literature by emphasizing on the conceptual framework, which is important to complement every empirical study.